Endobronchial ultrasound‐guided transbronchial needle aspiration for diagnosing mediastinal lymphadenectasis: a cohort study from a single center. (28th May 2015) - Zhu, Jun; Zhang, Hai‐ping; Ni, Jian; Gu, Ye; Wu, Chun‐yan; Song, Jiong; Ji, Xiao‐bin; Lu, Hai‐wen; Wei, Ping; Zhou, Cai‐cun; Xu, Jin‐fu
Abstract: Objective: Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is commonly used for clinical diagnosis of mediastinal lymphadenectasis. This study aimed to evaluate the diagnostic significance of EBUS‐TBNA for mediastinal lymphadenectasis in a large single center. Methods: A total of 846 patients who were not definitively diagnosed with mediastinal lymphadenectasis underwent EBUS‐TBNA were retrospectively analyzed in this study. Results: In total, 842 patients underwent EBUS‐TBNA successfully. There were 589 patients with malignancy, including squamous carcinoma (118 cases; 20.6%), adenocarcinoma (187 cases; 32.7%) and small cell carcinoma (88 cases; 15.4%). A total of 253 patients were diagnosed with benign disease, including tuberculosis (111 cases; 43.9%) and sarcoidosis (93 cases; 36.7%). The diagnostic sensitivity of lung cancer, tuberculosis and sarcoidosis were 94.4%, 81.1% and 51.6%, respectively. The overall sensitivity of EBUS‐TBNA was 92.0%. N2 stage in lung cancer patients who were diagnosed by EBUS‐TBNA was significantly higher than other stages. The positive rate of targeted puncture is high for the lymph nodes whose short‐axis diameters were larger than 1 cm. Conclusion: The operation risk of EBUS‐TBNA is relatively small. In diseases complicated by mediastinal lymphadenectasis, malignant diseases are most, and benign diseases mainly are granulomatous. EBUS‐TBNA is a valuable diagnostic technique in patients with mediastinal lymphadenectasis whose diagnosis have not been determined.